11-year results of pneumonectomies according to the regional cancer center - E. A. Toneev; R. F. Shagdaleev; V. D. Kulikov; A. A. Martynov; L. R. Zaripov; D. V. Glumnushina; N. D. Krymzalova; R. I. Lisyutin; A. Sh. Zulkarnyaev (Вестник хирургии имени И.И. Грекова)
The OBJECTIVE was to perform the survival analysis of patients after pneumonectomy.METHODS AND MATERIALS. The retrospective study included 93 patients with non-small cell lung cancer (NSCLC) who underwent pneumonectomy from 2014 to 2024.RESULTS. The average age of the patients who underwent surgery was 61 years. Squamous cell carcinoma was diag nosed in 50.5% of patients, adenocarcinoma – in 32.3 % of patients, other histological types – in 17.2 % of patients. 6 (6.4 %) patients died in the early postoperative period, of which 5 had right pneumonectomy. The overall 3- and 5-year survival rates were 50.57 % and 34.38 %, respectively, disease-free survival rate – 43.68 % and 32.18 %, respectively.CONCLUSIONS. In the structure of long-term outcomes in 40% of patients who underwent pneumonectomy, the cause of death was non-oncological pathology, most of the causes of non-oncological mortality were directly related to pneumonectomy.